Characteristics of healthcare workers infected with COVID-19: A cross-sectional observational study. (January 2021) - Al Maskari, Zaina; Al Blushi, Ahlam; Khamis, Faryal; Al Tai, Amal; Al Salmi, Issa; Al Harthi, Hasina; Al Saadi, Muzna; Al Mughairy, Ameera; Gutierrez, Ricky; Al Blushi, Zakariya
Highlights: Overall, 4.3% of healthcare workers (HCWs) at Royal Hospital, Muscat, Oman, tested positive for coronavirus disease 2019 (COVID-19) during the study period. There was no significant difference between hospital and community acquisition according to age, nationality, or presence of co-morbidities. There was a significant difference between hospital and community acquisition according to HCW category, sex, and being at risk of exposure to COVID-19 in the hospital. Overall, 78% of the infected HCWs had no chronic diseases and all made an uneventful recovery. Abstract: Introduction: Coronavirus disease 2019 (COVID-19) is a new emerging infectious disease, first identified in China in December 2019, caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). This study describes the characteristics of healthcare workers (HCWs) who tested positive for COVID-19 in a tertiary care hospital in Oman. Methods: This was a cross-sectional descriptive analysis of HCWs with COVID-19. Results: During the study period, 204 HCWs tested positive for COVID-19 by rRT-PCR test, with a test positivity rate of 21.2%; the percentage of infected hospital staff was 4.3%. Their mean age was 36 years. Overall, 2.2% of the male staff were infected, while 9.3% of the female staff were infected. Among the clinicians, 4.7% were infected; among the nurses, 4.1% were infected. Regarding acquisition, 61.3% of infections ( n = 125) were community-acquired and 25.5% ( n = 52) were hospital-acquired; no source was identified in 13.2% of cases ( n = 27). There was a significant difference between hospital-acquired and community-acquired COVID-19 according to the different HCW categories ( p < 0.001), sex ( p = 0.041), and being at risk of COVID-19 exposure in the hospital ( p < 0.001). There were no significant differences in relation to nationality ( p = 0498), age ( p = 0.119), or the presence of co-morbidities ( p = 0.326). Seventy-eight percent ( n = 160) had no chronic diseases and 44% presented with fever and an acute respiratory infection ( n = 90); all made an uneventful full recovery. The peak of infection acquisition was after the Eid Al Fitr festival. Conclusions: HCWs are at an increased risk of COVID-19 in the workplace. The strengthening of infection control measures to prevent exposures from infected patients and colleagues and to reduce the spread of COVID-19 is a necessity.